University Financial Support and Academic Ranking: Aspects of Interconnection - L. V. Prikhodko; A. N. Amerslanova; E. A. Kameneva (Финансы: теория и практика, 2024)
Increasing the competitiveness of Russian education is an important national strategic priority, enshrined within the framework of the national project “Education” and the concept of Russia’s humanitarian policy abroad. National and international academic rankings, despite the barriers that have arisen are a highly proven information resource in the world for all categories of participants in the higher education system.   The purpose of the study is to identify whether there is an interconnection between a university’s financial support and its position in academic rankings.   The authors use the classical correlation analysis, ranking and comparison of universities’ funding amounts and their position change in academic rankings. The examined development strategies, competitiveness improvement programs, sustainable development reports of the Russian and world’s universities that are constantly improving their positions in the world rankings. Based on the results obtained conclude that there is no direct interconnection between universities’ funding amounts and their positions in the rankings and a determining factor in the promotion of the universities in the academic rankings. For universities, direct competitive funding algorithms appear to be more effective in achieving the specific objective than regulatory funding. Russian universities seeking to advance in rankings focus on the combined application of mechanisms and sources of funding.